Evaluation of the safety and efficacy of TRAIL and taurolidine use on human fibrosarcoma xenografts in vivo - HARATI, KAMRAN (Oncol Lett, 2016)
Fibrosarcomas are rare malignant soft tissue tumours that exhibit a poor response to current therapeutic regimens. Previously, tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) and taurolidine were observed to induce apoptosis synergistically in HT1080 human fibrosarcoma cells in vitro. Consequently, the present study aimed to assess the safety and efficacy of TRAIL in combination with taurolidine on the local growth of fibrosarcoma xenografts in vivo. HT1080 fibrosarcoma cells were inoculated subcutaneously into both flanks of 49 athymic nude mice in order to establish tumour xenografts. TRAIL and taurolidine were applied intraperitoneally at various single and cumulative treatment doses. After 12 days, the experiment was terminated and surviving animals were euthanised. Tumour progression was determined during and following treatment. To assess the potential toxic effects of the two compounds, the organs (lung, liver, kidney and heart) of all animals were examined histologically. The results revealed that combined treatment with TRAIL and taurolidine significantly inhibited the growth of HT1080 xenografts, whereas untreated animals had steadily increasing tumours. The most effective combination was TRAIL at 2 µg per application (cumulative dose, 16 µg) and taurolidine at 30/15 mg per application (cumulative dose, 180 mg), reducing the mean size of implanted xenografts to 10.9 mm(2) following treatment (vs. 48.9 mm(2) in the control group; P=0.0100). Despite distinct tumour mass reduction, the rate of mortality was significantly increased in animals treated with TRAIL and taurolidine in a taurolidine dose-dependent manner; however, histological examinations of relevant organs revealed no evidence of systemic toxicity (mean survival time, 7.9 days in the treated groups vs. 12 days in the control group; P<0.0010). In summary, whilst the combination of TRAIL and taurolidine synergistically inhibited the growth of fibrosarcoma xenografts in vivo, it was also accompanied by significantly increased mortality rate. Thus, although taurolidine is assumed to be a compound with an acceptable toxicity profile, and therefore increasingly used in clinical trials, the current findings raise concerns with regard to its safety and therapeutic index, and indicate the requirement for further detailed toxicity tests.